The impact of human and spatial crowding on customer loyalty in Indonesia's trending sustainable restaurants: The mediating role of perceived value and brand management - Agustina Shinta Hartati Wahyuningtyas (Journal of Agricultural Socio-Economics (JASE), 2026)
One of the main external environmental factors influencing consumer behavior in the trending food sector is crowding, both human and spatial, where crowding can have both positive and negative effects on consumer repurchase intentions. To explore whether crowding conditions should be managed or left to unfold naturally, this study will compare the direct effect of crowding on customer loyalty and its effect through three main mediators of consumer perception. This study uses a questionnaire instrument with 36 indicators across eight variables, collected through interviews with 500 respondents aged at least 15 years who have visited trending restaurants in Indonesia during 2022-2024, using a 5-point Likert scale, and analyzed using SEM-PLS with WarpPLS 8.0 software. Brand management strategies in the food industry need to be carefully formulated to address crowding, especially in light of sustainability issues that consumers are increasingly aware of. Research shows that the effect of crowding on customer loyalty is stronger when mediated by the restaurant's sustainability perception, consumer perceived value, and word-of-mouth communication, compared to its direct effect. In crowding conditions, restaurant managers need to implement effective crowd management, increase perceived value, and strengthen sustainable brand management elements.